Dementia knowledge and associated factors among older Chinese adults: a cross-national comparison between Melbourne and Beijing. (24th October 2021) - Zhao, Mei; Lv, Xiaozhen; Lin, Xiaoping; You, Emily; Zhang, Haifeng; Ellis, Kathryn A.; Yu, Xin; Wang, Huali; Lautenschlager, Nicola T.
Abstract: Objectives: This study compared dementia knowledge between older Chinese adults in Melbourne, Australia, and Beijing, China, and explored factors associated with dementia knowledge between these two groups. Ultimately, this study aimed to inform the development of tailored dementia education programs for older Chinese adults. Design: A cross-sectional design was employed in this study. Setting: Participants were recruited from 5 Chinese community senior groups in Melbourne and 10 community health centers in Beijing from March to May 2019. Participants: A total of 379 older Chinese adults aged 50 and over completed the questionnaire, including 153 from Melbourne and 226 from Beijing. Measurements: Dementia knowledge was assessed using the Alzheimer's Disease Knowledge Scale (ADKS). Demographic characteristics, dementia-related experience, and the mental health status of participants were collected. Stepwise linear regression was used to analyze the factors associated with dementia knowledge. Results: In general, older Chinese adults in Melbourne and Beijing reported similar levels of dementia knowledge for both the overall ADKS scale (mean ± SD: 17.2 ± 2.9 in Melbourne vs. 17.5 ± 2.9 in Beijing, p > 0.05) and the seven subdomains. Of the subdomains, the highest correct response rates were observed in the life impact of the dementia subdomain, and the lowest rates were observed in the caregiving subdomain. Stepwise linear regression analysis revealed that younger age and self-reported dementia worry were significantly associated with higher levels of dementia knowledge in the Melbourne group, whereas a positive family history of dementia was significantly associated with higher levels of dementia knowledge in the Beijing group. Conclusions: Older Chinese adults living in Melbourne and Beijing share similar levels of dementia knowledge, but factors associated with their knowledge are different. These findings will inform the development of culturally and socially appropriate dementia education programs for older Chinese populations in different countries.